Dietary Magnesium Is Positively Associated With Skeletal Muscle Power and Indices of Muscle Mass and May Attenuate the Association Between Circulating C‐Reactive Protein and Muscle Mass in Women. (11th September 2015) - Welch, Ailsa A; Kelaiditi, Eirini; Jennings, Amy; Steves, Claire J; Spector, Tim D; MacGregor, Alexander
ABSTRACT: Age‐related loss of skeletal muscle mass and strength are risk factors for sarcopenia, osteoporosis, falls, fractures, frailty, and mortality. Dietary magnesium (Mg) could play a role in prevention of age‐related loss of skeletal muscle mass, power, and strength directly through physiological mechanisms or indirectly through an impact on chronic low‐grade inflammation, itself a risk factor for loss of skeletal muscle mass and strength. In a cross‐sectional study of 2570 women aged 18 to 79 years, we examined associations between intakes of Mg, estimated using a food‐frequency questionnaire (FFQ), dual‐energy X‐ray absorptiometry (DXA)‐derived measures of muscle mass (fat‐free mass as a percentage of body weight [FFM%], fat‐free mass index [FFMI, kg/m 2 ]), leg explosive power (LEP), and grip strength ( n  = 949 only). We also examined associations between circulating hs‐CRP (C‐reactive protein) and muscle mass and LEP, and explored the potential attenuation of these relationships by Mg. We compared our findings with those of age and protein intake. Endpoints were calculated by quintile of Mg and adjusted for relevant confounders. Significant positive associations were found between a higher Mg and indices of skeletal muscle mass and LEP, and also with hs‐CRP, after adjustment for covariates. Contrasting extreme quintiles of Mg intake showed differences of 2.6% for FFM% ( p trend < 0.001), 0.4 kg/m 2 for FFMI ( p trend = 0.005), and 19.6 watts/kg for LEP ( p trend < 0.001). Compared with protein, these positive associations were 7 times greater for FFM% and 2.5 times greater for LEP. We also found that higher hs‐CRP was negatively associated with skeletal muscle mass and, in statistical modeling, that a higher dietary Mg attenuated this negative relationship by 6.5%, with greater attenuation in women older than 50 years. No association was found between Mg and grip strength. Our results suggest that dietary magnesium may aid conservation of age‐related loss of skeletal muscle mass and power in women of all ages. © 2015 American Society for Bone and Mineral Research.